1 - The Land Act (1998) and Land Tenure Reform in Uganda: DOI: 10.4314/ad.v31i1.22248 - Okuku, Juma Anthony (Africa Development, 2006)
In agrarian societies land is not only the main means for generating a livelihood, it is also a means to accumulate wealth and transfer it between generations. In Uganda, it is a basic source of food, employment, a key agricultural input and a major determinant of a farmer’s access to other productive resources. The na- ture of land tenure, therefore, has profound implications for the development process of nations. As the historical experience of Europe, Asia, Latin America and Africa indicates, land tenure can either impede or facilitate positive socio- economic change in a given economy. The Land Act (1998), which aims at reforming land tenure relations in Uganda, is therefore one of the most far- reaching legislation enacted by the National Resistance Movement (NRM) gov- ernment. The new tenure system aims at supporting agricultural development through the functioning of a land market, establishing security of tenure and ensuring sustainable utilisation of land in order to bring about development. This paper discusses three major issues. First, the extent to which the new Land Act (1998) ensures security of tenure to the peasant majority in the country. Second, the issue of its capacity to resolve the long-run contestation between the mailo landowners and tenants (bibanja) holders. And third, the ambiguities and difficulties facing the Act in the process of its implementation must be con- fronted. The article is based on the textual analysis of the various land laws in Uganda historically. The literature brings out several constraints and ambigui- ties regarding the land reform process in Uganda.